A retrospective study of rectal prolapse in Chitwan Medical College - Bhattarai, Abhishek; Tamrakar, Kishore Kumar; Devkota, Pragya; Shah, Keshar Bahadur; Piya, Bimochan (Journal of Chitwan Medical College, 2018)
Rectal prolapse (RP) is an unusual anorectal disease affecting both children and adults. Complete rectal prolapse represents full thickness protrusion of the rectum through the anal verge. Incarceration and strangulation are the most unusual, but dreaded complications of rectal prolapse that requires a surgical emergency. Management of such complications is still controversial. Some prefer conservative management by application of sugar while other preferred operative intervention. When prolapse is not reducible and a sign of ischemia is present the operative intervention is inevitable. The choice of procedure also varies. The Altemeierperineal rectosigmoidectomy remains the best treatment of such emergency conditions.